MANGEMENTAL PRACTICES ADOPTED BY BUFFALO MILK PRODUCERS IN KRISHNA DISTRICT OF ANDHRA PRADESH - RANGAMMA, B.; JADESWARARAO, S.; PRASAD, R.M.V.; RAGAVARAO, E. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTA field survey was conducted to know the existing feeding and housing managementpractices by buffalo farmers in rural, semi-urban and urban areas of Krishna district. It wasfound that only 1.6 % farmers practiced chaffing of fodder. Paddy straw was sole roughageto buffaloes. No farmer practiced silage making and urea treatment of paddy straw. 26, 42and 68% farmers offered purchased concentrate feed, 80, 94 and 88 % offered concentratein soaked form in rural, semi-urban and urban areas, respectively. Regarding housingpractices 83, 67 and 56% farmers’ maintained buffaloes in loose house: 38, 51 and 68%had pucca floor: 23, 36 and 60% had pucca drainage facilities in rural, semi-urban andurban areas. 20% farmers provided cooling devices like fan in urban areas of the district.High cost of pure bred buffaloes, hired labour, feed ingredients, lack of financial assistancefor purchase of high milk producing buffaloes and equipment like chaffer cutter and lack ofextension activities was the major problems.Key worlds: Buffaloes, Feeding, Housing, Management Practices, Constraints.